Stalin - Woodcock, Sandra (London Hodder & Stoughton, 1998)
This is part of a series of material with a teenage or adult interest level for those with reading ages below 10, or for adult students learning English as a second or foreign language. The Real Lives selection offers biographies in the categories of sport, film, music, politics and history
Include Illustration
Keywords: Soviet Union -- Stalin, Joseph, 1878-1953 -- Heads of state